THEORETICAL STUDY OF NANOSTAR DENDRIMERS - SOLEIMANI, Najmeh; MOHSENI, Esmaeel; HELALBIN, Sahar (Studia Universitatis Babeș-Bolyai Chemia, 2016)
In this paper, we give some theoretical results about nanostar dendrimers by topological indices. Formulas for computing topological indices based on distance and degree in a graph such as eccentric connectivity, total eccentricity, fourth version of atom-bond connectivity and fifth version of geometric-arithmetic indices of two types of nanostar dendrimers are presented.